Safety and Efficacy of Oral and Parenteral Ibuprofen for Closure of Patent Ductus Arteriosus in Very Low Birth weight Asian Neonates - A retrospective Audit (Archives of Clinical and Medical Case Reports, 2021)
Introduction: Patent ductus arteriosus (PDA) is common in preterm neonates. Indomethacin and ibuprofen are commonly used for medical closure of patent ductus arteriosus. This study aims to evaluate the safety and efficacy of ibuprofen for treatment of PDA in very low birth weight (VLBW) infants. Methods: A retrospective audit of VLBW infants who received ibuprofen for treatment of PDA in a single centre between March 2010 and December 2014 was conducted. Infants with hemodynamically significant PDA were treated with intravenous or oral ibuprofen after echocardiographic evaluation. Response to treatment was documented with follow up echocardiography. The baseline patient characteristics, the ductal closure rate, adverse effects and need for PDA ligation were analysed. Results: Total of 138 VLBW infants received ibuprofen. 108 infants with birth weight ranging from 430-1500g received intravenous ibuprofen (group 1) and 30 infants with birth weight ranging from 661-1483g received oral ibuprofen (group 2). The closure rate of PDA was 50.9% (55/108) in-group 1 and 43.3% (13/30) in-group 2. Necrotizing enterocolitis or spontaneous intestinal perforation was observed in 11.1% (12/108) of group 1 and 10% (3/30) of group 2 infants. PDA ligation rate was 20.4% (22/108) in-group 1 and 6.7% (2/30) in-group 2. Conclusion: The closure rate of PDA following intravenous ibuprofen was 50.9% in VLBW infants. Serious gastrointestinal adverse effects occurred in 10-11% of infants treated with ibuprofen. Relatively lower closure rates and serious gastrointestinal adverse effects should be considered when treatment decisions are made for closure of PDA with ibuprofen.